Utterances and Enunciation in the Media Concerning Videogames: the concept of enlacements - Rocha, Décio (The ESPecialist, 2012)
This paper focuses on the discussion about the concept of enlacements as it is defined by Maingueneau. Through the investigation of the discourses built in the press about videogames in two different languages (Portuguese and French), we intend to offer a more adequate approach to the articulation between utterances and enunciation, on the basis of the analysis of different registers – enunciator and coenunciator, topography, cronography, ethos and language code – which circumscribe a particular position in a discursive field.